Qualification of Laser Based Additive Production for Manufacturing of Forging Tools - Junker, Daniel; Hentschel, Oliver; Schmidt, Michael; Merklein, Marion (Journal of Manufacturing Review, 2015)
Mass customization leads to very short product life cycles, so the costs of a tool have to be amortized with a low number of workpiecesEspecially for highly loaded tools, like those for forging, that leads to expensive productsTherefore more economical production processes for tool manufacturing have to be investigatedAs laser additive manufacturing is already used for the production of moulds for injection moulding, this technology maybe could also improve the forging tool productionWithin this paper laser metal deposition, which is industrially used for tool repair, will be investigated for the use in tool manufacturingTherefore a mechanical characterization of parts built with different laser process parameters out of the hot work tool steel 1.2709 is made by upsetting tests and hardness measurementsSo the influence of the additive manufacturing process on the hardness distribution is analysed
LFT Import::2019-08-05 (2110)